Les soins fondés sur la preuve : atteinte des compétences des étudiants de premier cycle en pharmacie - Beauchesne, Marie-France; Gardner, David; Ferreira, Ema; Bérard, Anick; Zed, Peter; Blais, Lucie (Pharmactuel, 2015)
-